Analysis Of Land Use Changes And Urban Land Value Zone Reviewed From The RDTR Plan Bandung - Sulistyo, Mohamad Adityo Ragil; Wijaya, Arwan Putra; Wahyuddin, Yasser (Departement Teknik Geodesi Universitas Diponegoro, 2022)
The city of Bandung, which is located in West Java Province, is known as the Flower City and consists of 31 sub-districts. One of the sub-districts in the city of Bandung which has various supporting facilities such as housing, rice fields, shopping centers, hospitals, and schools is Rancasari District. Rancasari Subdistrict, which is located in the south of Bandung City, every year always experiences rapid population growth and development from various aspects. These rapid changes and developments are also inseparable from the influence of detailed urban spatial plans and zoning regulations. The residential area is one of the things that is being considered, followed by other sectors that are starting to be built, such as trade and services, the main road that connects between cities, and the busy traffic causes the area to become congested. As a result, green land such as rice fields is reduced so that there is a lack of useful drainage to prevent flooding. In this study, it will be seen how changes in land value zones are affected by RDTR and zoning, in Rancasari District by referring to the Land Value Zone Map and Land Use Map so that they can identify and map the changes that occur every year to the land. The result of processing, in 2015, the highest land price in Cipamokolan Village was Rp. 2,602,000 namely in the Mixed class, Natural Protection, Public Services, Offices, Local Protection, and Housing.